2010
DOI: 10.1007/s00464-010-1197-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic surgery (SILS™) versus standard laparoscopic surgery: a comparison of performance using a surgical simulator

Abstract: SILS™ is more technically challenging than standard laparoscopic surgery. Using currently available SILS™ platforms and instruments, even surgeons with SILS™ experience are unable to match their overall LAP performance. Specialized training curricula should be developed for inexperienced surgeons who wish to perform SILS™.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
57
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 22 publications
7
57
1
2
Order By: Relevance
“…Although the results obtained may potentially have been influenced by these technical considerations, all participating surgeons used the same laparoscopic equipment. Our findings are consistent with clinical studies [8,9] and ergonomic analyses [10,11] showing that SILS is a more technically challenging surgery than standard multi-port laparoscopy. Moreover, the present results should be interpreted taking into account that experimental conditions are not directly comparable to real-life stress in individual patients where the environment can be more complex and demanding, further increasing mental and physical stress.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the results obtained may potentially have been influenced by these technical considerations, all participating surgeons used the same laparoscopic equipment. Our findings are consistent with clinical studies [8,9] and ergonomic analyses [10,11] showing that SILS is a more technically challenging surgery than standard multi-port laparoscopy. Moreover, the present results should be interpreted taking into account that experimental conditions are not directly comparable to real-life stress in individual patients where the environment can be more complex and demanding, further increasing mental and physical stress.…”
Section: Discussionsupporting
confidence: 92%
“…Physical and mental challenges between SILS and standard laparoscopy have been highlighted by different authors such as frequent instrument collisions, limited maneuverability, loss of triangulation, in-line viewing leading to unfamiliar angles of dissection and potential difficulty in reaching the intended target with instruments [10,11]. However, although the importance of minimally invasive surgery is constantly increasing most surgeons have limited knowledge of ergonomic aspects (physical and mental) of their work and additional data accrual and analysis are necessary [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fellows involved in the study did have prior experience in advanced multiport laparoscopic procedures, but their median operating time was similar to the time required by residents. These difficulties of conventional laparoscopic proficient surgeons to translate these skills to SILS have also been reported by three laboratory-based studies comparing laparoscopic-and SILS-trained candidates [16][17][18]. Pucher et al concluded that the skills required for SILS are not automatically acquired through multiport laparoscopic experience [19].…”
Section: Discussionmentioning
confidence: 93%
“…16 This coupled with steep Trendelenburg position made single incision surgeries possible. Byron F et al 17 reported a study which had compared the performance of standardized tasks from the fundamentals of laparoscopic surgery (FLS) program using either the regular laparoscopic or the single incision laparoscopic surgery (SILS) technique. His study demons trated that performing tasks using SILS techniques is more technically challenging even for surgeons with previous SILS experience.…”
mentioning
confidence: 99%